Pengaruh Lama Waktu dan Rasio Bola Penghancur Terhadap Karakteristik Produk Penggilingan Bata Merah - Hadi Nur Widianto; Ikhwanul Qiram; Anas Mukhtar (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2022)
The ball mill machine for grinding red brick waste is a tool for crushing red brick waste into powder. Factors that influence the production process are the length of time and the number of solid balls. This study aims to determine the effect of variations in the length of time and the comparison of the number of solid balls on the performance of the ball mill machine for grinding red brick waste. The method used in this study includes variations in the length of time and the ratio of the number of solid balls with a time of 10,15, and 20 minutes with a ratio of the number of solid balls 5:0, 5:5, 5:8 and 5:10. Measurement of the results of red brick powder using a wire-mesh with a size of 16; 60; and 100 mesh. The results showed that there was an effect of treatment variations in the length of time and the ratio of the number of solid balls to the production capacity of the red brick waste grinding machine. Where the highest value was obtained at a 5:0 ball ratio variation with an experimental length of 20 minutes with a mass difference of 104 grams, and the lowest result was obtained at a 5:5 ratio weighing 11 grams with an experimental time of 10 minutes.